Assessing the impact of demand shocks on the US term premium - Russell Barnett; Konrad Zmitrowicz (Bank of Canada, 2018)
During and after the Great Recession of 2008-09, conventional monetary policy in the United States and many other advanced economies was constrained by the effective lower bound (ELB) on nominal interest rates. Several central banks implemented large-scale asset purchase (LSAP) programs, more commonly known as quantitative easing or QE, to provide additional monetary stimulus. Gauging the effectiveness of LSAPs is important, since the ELB may be a constraint on conventional monetary policy more frequently in the future than it was in the past. In this paper we analyze two distinct periods where we observe exogenous demand shocks for 10-year US Treasury bonds to assess their impact on the term premium. Our results show that official sector demand factors, measured by purchases of securities by the foreign official sector and the Federal Reserve's asset purchase program, are important drivers explaining movements in the term premium. They suggest that asset purchases (QE) can help provide additional monetary stimulus even once the policy rate has reached its ELB. Robustness tests also suggest that the estimated impact of official sector demand factors is the most robust driver of the term premium across alternative specifications, while the estimates on risk factors appear more sensitive to the choice of term premium specification. Based on external projections and authors' assumptions, our results suggest that the US term premium will rise gradually from an average of about -20 basis points in the fourth quarter of 2016 to around +10, 32 and 60 basis points by the end of 2017, 2018 and 2019, respectively, before stabilizing around 100 basis points in the medium term.
Keywords: E; E4; E43; E5; E52; E58; E6; E61; E65; G; G1; G12; 330; Financial markets; Interest rates; Monetary policy framework; Monetary policy implementation; Transmission of monetary policy